HUBUNGAN PENGETAHUAN IBU HAMIL TENTANG TANDA BAHAYA KEHAMILAN DENGAN KETERATURAN MELAKSANAKAN ANTENATAL CAREDI PUSKESMAS PEMBANTUDAUH PURI DENPASAR TAHUN 2014 - SUKARTININGSIH, MARIA CHRISTINA ENDANG (Jurnal Kebidanan: MIDWIFERY MEDICAL JOURNAL, 2014)
Pregnant and delivery mortality or morbidity is the big problem in development countries, it’s about 25-50%. About 90% pregnant mother death caused in delivery and after delivery. Antenatal care is way to observe and support pregnant mother’s health. There was a lot of pregnant mother who has high risk in delivery and they should have to refer to hospital. This study aimed to know the relation between knowledge of pregnant mother about danger signs with regularity antenatal care. This study was analytic correlation with cross sectional. This study used 46 samples with purposive sampling. It’s collected by interview pregnant mother. Technique analyze used Chi-Square with p<0,05. Result of this study showed that Chi-Square value was 5,073 with p value 0,024 so there was relation between knowledge of pregnant mother about danger signs with regularity antenatal care in Puskesmas Pembantu Dauh Puri. There was significant relation between knowledge of pregnant mother about danger signs with regularity antenatal care.